(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Objective: Oral Lichen Planus (OLP) treatment or clinical management is challenging. This systematic review aims to discuss the main therapy used in the management of OLP and the efficacy of every type of treatment to improve the quality of patient life. Methodology: We discussed the publications on the clinical management of oral lichen planus on the PubMed database. Only randomized controlled trials (RCT) conducted in humans were considered. We included randomized controlled trials (RCT) published from 2005/1/1 to 2021/5/28 with symptomatic, clinically, or histologically diagnosed OLP. We compared different active treatments or between active treatment and placebo. Results: Twenty randomized controlled trials involving 931 patient samples were included in the analysis. For the short time treatment (on average 2-8 weeks) of OLP, TCI, including Tacrolimus, pimecrolimus, and Ciclosporin, were similar to TCS, including Clobetasol, triamcinolone in efficacy. Tacrolimus–Triamcinolone resulted in similar outcomes. In addition, Tacrolimus and Ciclosporin showed a statistically higher incidence of local adverse events than triamcinolone and Clobetasol. A few systemic adverse events occurred in the tacrolimus and ciclosporin groups, but they were not serious. Conclusion: Triamcinolone acetonide 0.1% should be the first drug of choice when selecting TCS, and Tacrolimus 0.1% should be the drug of choice when selecting TCI. J Bangladesh Coll Phys Surg 2023; 41: 219-233